(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The concept of language and letters in Ibn Arabi’s thought encompasses the entirety of existence from its highest to its lowest levels ranging from the realm of divinity and absolute imagination to the realm of creation and transformation. All levels of existence emanate from the ʿamāʾ (the Divine Cloud), which represents the Divine Self and constitutes one of the degrees of absolute imagination. There exists, therefore, a parallelism between the degrees of existence and the Divine Names on the one hand, and the letters of language on the other. In this way, the twenty-eight Divine Names correspond to twenty-eight ontological degrees, which in turn correspond to the twenty-eight letters of language. Ibn Arabi also attributes to the long vowels a symbolic relation to these degrees a relation that both affirms separation and implies interpenetration. These vowels belong to a realm analogous to ours yet are neither within it nor outside it. This conception aligns with Ibn Arabi’s analogy between the movements (vowels) and the realm of absolute imagination or divinity.